Solution-focused therapy : theory, research & practice - Macdonald, Alasdair J. (SAGE, 2011)
This is the only comprehensive yet accessible introduction to the history, theory, research and practice of solution-focused therapy (SFT) within mental health care and beyond. This new edition draws on contemporary research, recent developments in SFT training and the integration of SFT with other approaches